2008
DOI: 10.1530/eje-08-0142
|View full text |Cite
|
Sign up to set email alerts
|

Somatotropic responses to soy protein alone and as part of a meal.

Abstract: Context: GH is an important regulator of growth and body composition. We previously showed that GH release can be promoted by oral ingestion of soy protein; it is not known, however, whether these somatotropic effects of soy protein are also present when soy protein is ingested as part of a complete meal. Objective/design: We compared the effects of oral ingestion of soy protein alone with the effects of a meal containing the same amount of soy protein on GH secretion in six healthy women (body mass index 19-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, it should be noted that many of the studies performed in rodents investigated short-term effects of high doses of purified isoflavone or soy protein extracts (30-40% soy protein) [62]. In addition, the somatotropic effect of soy proteins is reduced when ingested as part of a meal instead of alone [28]. These observations may explain in part the modest results observed in the present study where the 20% soy content was mixed with other nutrients in the chow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that many of the studies performed in rodents investigated short-term effects of high doses of purified isoflavone or soy protein extracts (30-40% soy protein) [62]. In addition, the somatotropic effect of soy proteins is reduced when ingested as part of a meal instead of alone [28]. These observations may explain in part the modest results observed in the present study where the 20% soy content was mixed with other nutrients in the chow.…”
Section: Discussionmentioning
confidence: 99%
“…Soy and isoflavone dietary supplementation were reported to protect from cardiovascular diseases and maintain bone mineral density in postmenopausal women [26,27]. In humans, ingestion of a soy protein drink [0.6 g/kg body weight (BW)] stimulates GH secretion [28]. Moreover, consumption of a soy-rich diet, deficient in iodine, was shown to increase the number of thyroid-stimulating hormone, prolactin and GH-immunoreactive cells in the rat anterior pituitary [29].…”
Section: Introductionmentioning
confidence: 99%
“…High-protein meals produce increased cortisol concentrations [ 52 ], which in turn may increase insulin resistance and insulin requirements. Meals that are high protein and low CHO produce increased growth hormone levels; however, when the meal contains significant amounts of CHO, growth hormone is unchanged or decreased [ 53 ]. Meals high in protein increase circulating IGF-1 levels and decrease ghrelin levels [ 54 ].…”
Section: Proteinmentioning
confidence: 99%
“…High levels of insulin and insulin treatment in diabetic patients on the other hand are known to decrease circulating GH (17,18). Several investigations in the past have demonstrated that especially protein intake is crucial for an intact GH/IGF system (19,20), and it is well known that a high protein intake as well as individual amino acids can stimulate GH release in healthy subjects (21,22). Diets high in fat have been shown to inhibit GH secretion, most likely due to stimulation of somatostatin (16).…”
mentioning
confidence: 99%